Functional outcome of small and long bone lengthening by distraction osteogenesis - Nara, Srikanth; Bhat, Anil K.; Vidiyala, Sharath Chandra (International Journal of Research in Orthopaedics, 2017)
Background: Upper limb lengthening has limited indications because of the predominant non weight bearing nature. However, lengthening does have specific indications where the functional outcomes improve in selected patients. The aim of the study was to compare the clinical and radiological outcomes of upper limb long and short bone lengthening by distraction osteogenesis. Methods: A total of twenty four lengthenings were done in 21 patients, three cases being bilateral. The study group included cases of club hand, symbrachydactyly, multiple hereditary osteocondramatosis, traumatic amputations and congenital defects. Operative technique involved gradual mechanical distraction by orthofix external fixator after osteotomy. Clinical and radiological evaluation was done on follow up. The functional outcome for daily activities was assessed. The Healing index, Percentage healing index and Consolidation time were calculated. Results: The mean age of patients was 11.6 years. The percentage healing index of long bones was higher compared to short bones but the consolidation time was almost similar. Complications were seen in 35% patients. The satisfaction rates were higher in small bone lengthening and the complication rates were almost same as for long bones. Grasp, pinch strength and range of motion improved in cases of short bone lengthening. Conclusions: Distraction osteogenesis is reliable and predictable method of correction of osseous defects with vascular bone without sacrificing any adjacent digits or toes. It also gains soft tissue that is sensate with good blood supply.